Spatial scan statistics and identification of high-risk areas for COVID-19 in the state of Bahia, Brazil - Marques Bezerra, Ronney; Santana, Gibson Barros de Almeida Santana; Cavalcanti Leal, Thiago; Gomes Santos, Lucas; Ferreira Machado, Michael; Xavier, José Emerson; Fernandes, Tânia Rita Moreno de Oliveira Fernandes; Armstrong, Anderson da Costa; dos Santos, Allan Dantas; Bezerra-Santos, Márcio; Nunes, Bruno Eduardo Bastos Rolim; Vieira Santos, Giulia; et al. (Revista Portal: Saúde e Sociedade, 2022)
Introduction: The number of COVID-19 cases in Brazil has increased substantially in all regions of the country. The North and Northeastern region of Brazil has been severely affected by COVID-19, with high mortality rates. The first case of COVID-19 in northeastern Brazil was confirmed in the state of Bahia. The state is also the largest in the region in terms of area and population size. The study aimed to analyze the spatial distribution of incidence and mortality rates due to COVID-19 in the state of Bahia, Brazil. Methods: An observational study was carried out with COVID-19 data accumulated on May 16, 2020. Global and local Moran statistics and spatial scan statistics were used. Results: Between March 6, 2020 and May 16, 2020 there were 8,288 confirmed cases and 284 deaths (1.9/100,000) of COVID-19 in Bahia state. Over that time frame the incidence risk of disease was 55,7 (95%CI 54,1-58,2) per 100,000 individuals at risk. The mortality rate is 1.9 per 100,000 (95%CI 1,81-1.98). The spatial scan statistics identified five high-risk clusters for incidence rate, among which cluster 1 stood out, with 86 municipalities. This cluster accounts for 85.24% of all cases registered in the state, and it has a RR of 10.6. Conclusion: The study showed heterogeneous distribution of occurrence and death in Bahia, with areas of higher relative risk in the east and south. Actions to fight the disease in the state must take into account the risk areas identified in the study. Keywords: coronavirus; COVID-19; epidemiology; SARS-CoV-2; spatial analysis.